Seychellister mornicus, a new genus and species of Clavigeritae (Coleoptera, Staphylinidae, Pselaphinae) from Seychelles - Hlaváč, Peter; Nakládal, Oto (Zootaxa, 2018)
Seychellister mornicus, gen. and sp. nov. is described based on three specimens collected by sifting of leaf-litter in Mahé, Seychelles. The genus is tentatively placed in the subtribe Clavigerodina (Pselaphinae: Clavigeritae: Clavigerini).